Mechanical stress-mediated immune and inflammatory regulation: a bibliometric and visualization analysis of mechanoimmunology based on two databases - Pang, Jiayuecheng; Ma, Yicheng; Huang, Hongchao; Ma, Jiqing; Zheng, Yongjun; Xiao, Shichu; Xia, Zhaofan (Frontiers in Medicine, 2025)
BackgroundWith advances in detection technologies and the trend of interdisciplinary integration, mechanical stress in biomechanics has been shown to exert broad effects on organisms. It influences multiple cellular processes, including proliferation, migration, and differentiation, and also plays a critical regulatory role in both immune cell function and the organismal immune-inflammatory response. Thus, an emerging interdisciplinary field—mechanoimmunology—has emerged. However, the specific mechanisms underlying this field remain incompletely elucidated. Herein, this study aims to identify the latest research hotspots and provide a thorough analysis of the current research status in this domain.MethodsA total of 1,901 articles were retrieved from the Web of Science Core Collection (WOSCC) and 2,954 articles from Scopus. These selected articles were imported into bibliometric analysis software for preliminary data processing, followed by further visual analysis using multiple graphing tools. Finally, specific analyses were conducted based on various categories, including journals, authors, geographical distribution, citations, and keywords.ResultsThe United States and China are the two leading research hubs in this field, with the University of California System currently standing as the most influential institution. A surge in research on mechanoimmunology has been observed since 2021. During the “Research Explosion Phase” post-2021, several new keyword clusters emerged, including “T cells,” “macrophage polarization,” and “ion channels,” alongside clusters related to emerging fields such as “wound healing,” “gut microbiota,” and “bone remodeling.” The mechanosensitive ion channel protein Piezo1 and the YAP/TAZ transcription complex in the Hippo pathway have emerged as key targets in recent studies.ConclusionThis study identifies the ongoing research surge in the field of mechanoimmunology while comprehensively delineating the current research landscape. Additionally, through keyword clustering across different phases, it uncovers the latest research hotspots and potential future research directions focused on novel mechanosensitive targets for immune-inflammatory modulation. This work provides a clear research roadmap for investigators in the field, offering insights into future research possibilities.